Endothelial Function and Arterial Stiffness Should Be Measured to Comprehensively Assess Obstructive Sleep Apnea in Clinical Practice - Luo, Jinmei; Wang, Xiaona; Guo, Zijian; Xiao, Yi; Cao, Wenhao; Zhang, Li; Su, Linfan; Guo, Junwei; Huang, Rong (Frontiers in Cardiovascular Medicine, 2021)
Objective: An effective clinical tool to assess endothelial function and arterial stiffness in patients with obstructive sleep apnea (OSA) is lacking. This study evaluated the clinical significance of subclinical markers for OSA management in males without serious complications. Patients/Methods: Males without serious complications were consecutively recruited. Clinical data, biomarker tests, reactive hyperemia index (RHI), and augmentation index at 75 beats/min (AIx75) measured by peripheral arterial tonometry were collected. An apnea hypopnea index (AHI) cutoff of ≥15 events/h divided the patients into two groups. Results: Of the 75 subjects, 42 had an AHI ≥ 15 events/h. Patients with an AHI ≥ 15 events/h had higher high-sensitivity C-reactive protein, tumor necrosis factor-alpha (TNF-α), vascular endothelial growth factor, and AIx75 values than the control group but no statistical difference in RHI was observed. After controlling for confounders, TNF-α was negatively correlated with the average oxygen saturation (r = −0.258, P = 0.043). RHI was correlated with the rapid eye movement (REM) stage percentage (r = 0.306, P = 0.016) but not with AHI (P > 0.05). AIx75 was positively correlated with the arousal index (r = 0.289, P = 0.023) but not with AHI (r = 0.248, P = 0.052). Conclusions: In males with OSA without severe complications, TNF-α and AIx75 are independently related to OSA. The role of RHI in OSA management requires further elucidation. These markers combined can comprehensively evaluate OSA patients to provide more evidence for the primary prevention of coronary heart disease and treatment response assessment.